Development of Metaverse-Based Virtual Reality Counseling: Technology-Assisted Psychological Services for Students with Disabilities - Ariffudin, Imam; Hudha, Muhammad Nur; Zaini, Akhmad; Rahmawati, Ajeng Intan Nur (Jurnal Kajian Bimbingan dan Konseling, 2024)
This study aims to develop a metaverse-based Virtual Reality Counseling (VRC) medium to support psychological services for students with special needs. The research method used is the research and development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results show that the metaverse-based VRC medium has met the media acceptability aspects, making it feasible for effective implementation. Additionally, experimental results indicate a decrease in the levels of mental health disorders experienced by the counselees after undergoing individual counseling assisted by the metaverse-based VRC medium. The impact of this study suggests that the metaverse-based VRC medium is effective as a supporting medium in providing psychological services to students with special needs. The novelty of this research lies in the application of metaverse technology, which provides a more immersive and interactive counseling experience while addressing various limitations of conventional counseling services. The integration of the metaverse in counseling services offers time and place flexibility and allows for the creation of scenarios and simulations that can help students more effectively address their issues. Thus, this research paves the way for the development of more inclusive and adaptive psychological services tailored to the special needs of students.